Utilization of gamma irradiated emulsified frying oil wastes as a carbon source for sustainable and economical production of bacterial cellulose membrane - Doaa A. Hamed (BMC Microbiology)
Abstract Background Bacterial cellulose (BC) is a nanofibrils macromolecule that possesses unique properties and versatile applications in various fields. For commercial production, agro-industrial wastes were used as sustainable and cost effective alternative sources. Annually, a great amount of frying oil wastes are produced worldwide and disposed illegally resulting in huge environmental disasters. In this regard, the study aimed to investigate the effect of different concentration and increasing doses of gamma irradiation on the potential utilization of emulsified FOW as carbon source for BC production. In addition to tracking the behavior of SCOBY and BCM formation process in the presence of FOW. Methodology The effect of different factors including; concentrations of FOW, incubation period emulsification ratios and gamma irradiation on BC production were investigated and estimated gravimetrically. In addition, the manner of the cellulose membrane formation was closely tracked and was documented by photos. Results The data proved that the symbiotic culture (SCOBY), has the ability to utilize frying oil wastes as a sole carbon source. Addition of 1% FOW resulted in (12.1%) increasing the BCM dry weight (2.81 to 3.15 gL- 1 in SWM, while the addition of 1% of the emulsified oil (FOW/E) recording (32.6%) increase in BC dry weight compared with control (5.33 and 4.02 gL- 1, respectively). Further increase in FOW/E concentration (> 2–5%) resulted in a significant gradual decreases (39%) in BC dry weight (from 5.33 to 3.25 gL- 1). Whereas, increasing the incubation period (21- days) resulted in a significant increase in BCM dry weight from 3.79 to 5.32 gL- 1 (40.4%). The effect of gamma irradiation (0–50 kGy) of FOW/E showed an increase in BCM dry weight (2.5%) at dose 10 kGy, while recorded (34.1%) increase compared with control (without FOW). The critical moments of SCOBY while struggling for surviving to gain the oxygen and nutrients required for BC biosynthesis in the presence of FOW have been documented photographically. Conclusion The present study positively contributes to the field of BC biosynthesis, where the FOW was added to the other agro-industrial wastes as a source of carbon for BC production, in addition to its potential application in the future in bioremediation for controlling environmental pollution.